2004
DOI: 10.1002/ajim.10331
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of silicosis among stone carvers in Brazil

Abstract: Exposure to high levels of silica dust was associated with an increased prevalence of silicosis among stone carvers. Am. J. Ind. Med. 45:194-201, 2004.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
1
20
1
1
Order By: Relevance
“…DLCO results are divergent in other reports. In one report it was normal in workers who were heavily exposed to silica [Antao et al, 2004]; in another it was significantly reduced in 76 patients with silicosis [Ooi et al, 2003]. In our population, DLCO did not correlate with duration of exposure or chalk use.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…DLCO results are divergent in other reports. In one report it was normal in workers who were heavily exposed to silica [Antao et al, 2004]; in another it was significantly reduced in 76 patients with silicosis [Ooi et al, 2003]. In our population, DLCO did not correlate with duration of exposure or chalk use.…”
Section: Discussionmentioning
confidence: 66%
“…In a similar study, stone carvers who had worked more than 15 years shown a higher prevalence of silicosis [Antao et al, 2004].…”
Section: Discussionmentioning
confidence: 96%
“…These two cases were the ones with the longest exposure times. Antao et al reported a relationship between the intensity of the opacities seen in HRCT and functional impairment 10) . According to radiological findings and pulmonary function test parameters the most severe effect was seen in Case 1 who eventually died due to respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…(12) A identificação de micronódulos, a presença de coalescên-cia de nódulos e a existência de enfisema, que habitualmente ocorrem nas regiões superiores e posteriores dos pulmões, são melhor visualizadas na tomografia computadorizada de tórax de alta resolução, quando comparada com a radiografia e a tomografia convencional. (12,(15)(16) Entretanto, seu emprego deve ser reservado como método de diagnóstico complementar nos casos duvidosos (Classificação OIT 0/1 ou 1/0) ou para auxiliar no diagnóstico diferencial com outras doenças, especialmente a sarcoidose e a linfangite carcinomatosa. (14,17) A biópsia pulmonar só está indicada na presença de alteração radiológica com ausência de dados na história ocupacional que sugiram a associação.…”
Section: Diagnósticounclassified